2020
DOI: 10.1002/14651858.cd009628.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Structural magnetic resonance imaging for the early diagnosis of dementia due to Alzheimer's disease in people with mild cognitive impairment

Abstract: BackgroundMild cognitive impairment (MCI) due to Alzheimer's disease is the symptomatic predementia phase of Alzheimer's disease dementia, characterised by cognitive and functional impairment not severe enough to fulfil the criteria for dementia. In clinical samples, people with amnestic MCI are at high risk of developing Alzheimer's disease dementia, with annual rates of progression from MCI to Alzheimer's disease estimated at approximately 10% to 15% compared with the base incidence rates of Alzheimer's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 383 publications
2
95
1
1
Order By: Relevance
“…1,4 However, conventional MRI methods alone are often limited in their sensitivity to underlying neuropathological changes. 4 In particular, standard structural imaging demonstrates brain atrophy on a gross tissue level, although more advanced analysis with voxel-based morphometry (VBM) can highlight subtle brain volumetric changes. 5 Advanced multimodal neuroimaging approaches, including diffusion-weighted MRI, can provide novel metrics related to functional changes associated with AD.…”
mentioning
confidence: 99%
“…1,4 However, conventional MRI methods alone are often limited in their sensitivity to underlying neuropathological changes. 4 In particular, standard structural imaging demonstrates brain atrophy on a gross tissue level, although more advanced analysis with voxel-based morphometry (VBM) can highlight subtle brain volumetric changes. 5 Advanced multimodal neuroimaging approaches, including diffusion-weighted MRI, can provide novel metrics related to functional changes associated with AD.…”
mentioning
confidence: 99%
“…The validation of biomarkers is imperfect, and they might not be sufficiently sensitive or specific for the clinical syndrome [49]. In research cohorts, the classification accuracy of MRI biomarkers varies, but appears to improve when using multiple MRI biomarkers combined or quantitative methods instead of visual MRI ratings [21,[90][91][92]. CSF biomarkers appear to have better sensitivity than specificity proposing greater utility to exclude AD etiology than include [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its long history, relying on structural MRI for the early diagnosis of Alzheimer’s disease in the form of mild cognitive impairment (MCI) is not currently recommended. A recent Cochrane review found a high false negative rate of 27% and a false positive rate of 29% [ 10 ] based on data from 33 studies. Most of the data came from studies looking solely at the hippocampus although overall the data quality was sparse with insufficient data available to establish whether, for example, total brain volume could better differentiate between MCI and Alzheimer’s disease.…”
Section: Structural Imagingmentioning
confidence: 99%